2011
DOI: 10.22401/jnus.14.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antioxidant Levels (Vitamin E &Selenium) In Serum of Polycystic Ovary Syndrome Patients and Control

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder of reproductive women. The antioxidant (Vitamin E and Selenium) have important role in infertility and in PCOS. The aim of this study, to know the role of Vitamin E and Selenium during the phases of menstrual cycle and its effect on ovulation in (PCOS) patients and effect of body mass index in PCOS patients. This study, include 25 untreated and 26 treated PCOS patients comprised with 42 control. Vitamin E and selenium were measured by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Different antioxidants, endogenous and exogenous [6] and their dietary sources [55] listed here are not absolute. Besides, vitamin E, a fat-soluble vitamin with high antioxidant potency, enhances ovulation in PCOS women [56] and prevents CVD [57]. The dietary sources of vitamin E are vegetable oils, wheat germ oil, nuts, cereals, fruits and eggs.…”
Section: Antioxidantsmentioning
confidence: 99%
“…Different antioxidants, endogenous and exogenous [6] and their dietary sources [55] listed here are not absolute. Besides, vitamin E, a fat-soluble vitamin with high antioxidant potency, enhances ovulation in PCOS women [56] and prevents CVD [57]. The dietary sources of vitamin E are vegetable oils, wheat germ oil, nuts, cereals, fruits and eggs.…”
Section: Antioxidantsmentioning
confidence: 99%
“…The participants in this sample included 25 PCOS patients who were untreated and 26 PCOS patients who were treated, as well as 42 healthy controls. From the results of this study, it was found that vitamin E has a significant role in the ovulation of PCOS patients [71]. Angiogenesis disturbances are common in women with polycystic ovary syndrome (PCOS).…”
Section: Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 85%